ENHANCING ADOLESCENTS' EMERGENCY RESPONSE CONFIDENCE THROUGH FIRST AID TRAINING IN TUBAN - MOH. UBAIDILLAH FAQIH; KARYO KARYO; KUSNO FERIANTO; DWI KURNIA PURNAMA SARI (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Adolescents living along the Pantura Highway in Tuban are frequently exposed to road traffic accidents but generally lack adequate first aid knowledge and confidence to provide emergency assistance. Strengthening adolescents' confidence through community-based first aid training is essential to improve pre-hospital emergency response. Objective: This community service program aimed to enhance adolescents' confidence and practical first aid skills through simulation-based training. Methods: A simulation-based educational program was conducted from May to June 2025 involving 40 adolescents aged 15–19 years residing along the Pantura Highway in Tuban. The program consisted of three stages: pre-activity preparation, training implementation, and evaluation. Learning methods included interactive lectures, instructor demonstrations, hands-on practice, and scenario-based simulations following Basic Life Support and first aid guidelines. Program effectiveness was evaluated using pre- and post-training questionnaires assessing self-confidence and knowledge, supported by direct observation of practical skills during simulation sessions. Results: Most participants (72.5%) had never attended previous first aid training. Before the intervention, 60.0% of participants reported low self-confidence, while only 7.5% demonstrated high confidence. After the training, the proportion of participants with low confidence decreased to 12.5%, whereas those with high confidence increased to 47.5%. Participants also demonstrated better performance in emergency scene assessment, cardiopulmonary resuscitation, bleeding control, victim evacuation, and communication with emergency medical services during simulation exercises. The combination of repeated practice and realistic emergency scenarios effectively improved participants' confidence, psychomotor competence, and readiness to respond to emergency situations. Conclusion: Simulation-based first aid training is an effective community empowerment strategy for improving adolescents' confidence and preparedness in emergency response. Regular implementation through collaboration among schools, healthcare institutions, youth organizations, and local governments is recommended to establish sustainable community-based emergency preparedness programs in high-risk traffic areas.